China’s Balancing Act in the Western Sahara Conflict - Zhou, Hang (Africana Studia, 2020)
Despite China’s growing interests in African peace and security, its role in the Western Sahara conflict remains detached, distanced, and largely confined to its participation in UNSC debates and MINURSO. This is partly explained by the limited China’s overseas interests in Western Sahara. In the absence of significant conflict escalation, the status quo in Western Sahara allows Beijing’s continued pursuit of economic cooperation with both Algeria and Morocco. Primarily through a realpolitik lens, Beijing does not see the current conflict irresolution posing significant risks to its economic, geopolitical and security interests in the wider North-western African region. Therefore any significant changes in Beijing’s position on West Sahara remains unlikely in the near future. Keywords: China, Western Sahara, MINURSO, foreign and security policy.